Acute Coronary Syndrome in Young Patients at Dr. Sardjito General Hospital - Setianto, Budi Yuli; Sari, Julia; Hartopo, Anggoro Budi; Gharini, Putrika Prastuti Ra (Acta Interna The JOurnal of Internal Medicine, 2014)
ABSTRACTBackground: The incidence of acute coronary syndrome in the young patients is increased recently.Several studies reported that young patients have distinct clinical characteristics as compare with olderpatients.Objective: To assess the prevalence, risk factors and clinical presentation of acute coronarysyndrome(ACS) in young patients at Dr. Sardjito Hospital, Yogyakarta.Methods: We conducted a cross sectional study between September 2008-May 2009 at intensivecardiovascular care unit (ICCU) of Dr. Sardjito Hospital. We enrolled consecutive patients admittedwith acute coronary syndrome. We divided the patients as young ACS (age â¤ 45 years) and older ACS(age >45 years). We compared cardiovascular risk factors, clinical presentation and clinical spectrumsfrom both groups. Statistics analysis was performing using chi-square test, p value < 0.05 was consideredsignifi cantly different.Results: In our study there were 20 (13.5%) young ACS and 128 (86.5%) older ACS patients. Mostyoung ACS patients are male (90%). Proportion of diabetes mellitus in young ACS was not differentfrom that in older ACS patients (20% vs. 18.8%; p=0.55). Hypertension was not different either (50%vs. 53.1%; p=0.49). Sixty percent of young ACS patients were smoker, however its proportion did notdiffer from older ACS patients (p=0.84). There were no signifi cant differences of dyslipidemia. Theyoung ACS patients mostly experienced STEMI than NSTEMI and unstable angina (55% vs. 15%vs. 30%), but there were no signifi cant differences when compared to older ACS patients (p=0.65).Thirty percent of young ACS patients presented with Killip class II or higher, however there were nosignifi cant differences between groups (p=0.40).Conclusion: In this study we found that there were no signifi cant differences in risk factors, clinicalpresentation and spectrums between young ACS and older ACS patients. The need for preventionprogram in both groups should not be difference.Keywords: ACSâ youngâ olderâ clinical presentation.